2013
DOI: 10.1152/japplphysiol.00925.2012
|View full text |Cite
|
Sign up to set email alerts
|

Calpain and caspase-3 play required roles in immobilization-induced limb muscle atrophy

Abstract: Talbert EE, Smuder AJ, Min K, Kwon OS, Powers SK. Calpain and caspase-3 play required roles in immobilization-induced limb muscle atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 31 publications
3
60
0
1
Order By: Relevance
“…This suggests that apoptosis would be a biological process promoting atrophy through a loss of myonuclei during immobilization. Such idea is supported by studies demonstrating that caspase-3 activity [59,89] and the apoptotic mitochondrial intrinsic pathways (i.e., endonuclease G and apoptosome) [86,90] are stimulated in unloaded skeletal muscle.…”
Section: Cellular Mechanisms Involved In Immobilization-induced Skelementioning
confidence: 92%
See 1 more Smart Citation
“…This suggests that apoptosis would be a biological process promoting atrophy through a loss of myonuclei during immobilization. Such idea is supported by studies demonstrating that caspase-3 activity [59,89] and the apoptotic mitochondrial intrinsic pathways (i.e., endonuclease G and apoptosome) [86,90] are stimulated in unloaded skeletal muscle.…”
Section: Cellular Mechanisms Involved In Immobilization-induced Skelementioning
confidence: 92%
“…In skeletal muscle, recent studies demonstrated that both calpains and caspase-3 were activated by hindlimb unloading [59,95,96]. Interestingly, pharmacological inhibition of calpains or caspase-3 prevents type I fibers atrophy observed in casted rats, demonstrating that these proteases are mandatory for skeletal muscle atrophy [89].…”
Section: Cellular Mechanisms Involved In Immobilization-induced Skelementioning
confidence: 99%
“…Although the causes of disuse-induced oxidative stress in skeletal muscle continues to be investigated, evidence suggests that prolonged skeletal muscle inactivity results in increased superoxide production at multiple locations in the cell including NAD(P)H oxidase, xanthine oxidase, and the mitochondria [20-24]. In regard to the relative contributions of each of these sources of ROS production, recent evidence suggests that mitochondria are a major source of ROS production in inactive skeletal muscles [20, 21, 25]. For example, compared to mitochondria obtained from skeletal muscles of active rodents, mitochondria from muscle exposed to prolonged periods of disuse release significantly more ROS [26] [20, 24].…”
Section: Sources Of Ros and Rns In Atrophying Skeletal Musclementioning
confidence: 99%
“…The calpain family of proteins is calcium dependent proteases that are important in the initiation of the breakdown of actin, myosin, and other structural proteins. Indeed, target pharmacological inhibition of calpain protects against disuse muscle atrophy (Tischler et al, 1990; Goll et al, 2003; Maes et al, 2007; Nelson et al, 2012; Talbert et al, 2013a). Caspase-3 is a member of the cysteine-aspartic acid protease family.…”
Section: Overview Of the Regulation Of Muscle Sizementioning
confidence: 99%